Effects of 1-Methylcyclopropene, Gibberellic Acid, and Aloe vera Coating on Lime Storage Life and Fruit Quality - Ladawan Lerslerwong; Chompoonut Buapuean; Adirek Rugkong; Kanokporn Bunya-Atichart (My University, 2023)
Limes (Citrus aurantifolia Swingle) have a short postharvest life. Therefore, effective treatments increasing storage life to lengthen the time that produce remains fresh is desirable. This study evaluated the effects of postharvest treatments of 1-methylcyclopropene (1-MCP), gibberellic acid (GA3), and Aloe vera on lime storage life and fruit quality. The optimum individual treatments of 50% Aloe vera coating, 300 mL·L−1 GA3, and 750 nL·L−1 1-MCP were identified as most effective in extending lime postharvest life. Under ambient conditions (26.4 ± 1.0°C, 64.4 ± 7.4% RH), 1-MCP fumigation was the best treatment, increasing lime postharvest life to 28.2 days. The 1-MCP-treated fruit had a higher juice content than the control fruit. Also, soluble solid contents and titratable acidity were not significantly different, while ascorbic acid was lower than the control. Under cold room conditions (10.0 ± 0.3°C, 68.9 ± 12.4% RH), 1-MCP fumigation followed by Aloe vera coating was the best treatment, increasing lime storage life by 38.7 days. The longer storage time did reduce juice content in treated limes compared to untreated fruit. However, the treatment did not affect the soluble solid contents, titratable acidity, or ascorbic acid level. In conclusion, for optimum postharvest life in limes stored under ambient conditions, fumigation with 1-MCP is best. While for limes stored in cold rooms, a cotreatment of 1-MCP fumigation followed by Aloe vera coating maximizes postharvest life.
Keywords: Aloe Vera; Titratable acid; 1-Methylcyclopropene; Gibberellic acid; Postharvest Quality and Shelf Life Management